Electrochemical Polymerization of Guaiacol in Organic Solvents and Analytical Performance of the Poly (Guaiacol) Modified Electrode Towards Phenol Antioxidants - László Kiss; Péter Szabó; Sándor Kunsági-Máté (Chemosensors, 2025)
The electrochemical polymerization of guaiacol was studied in different organic solvents. Significant electrode blocking was observed in dichloromethane. Microscopic studies verified the formation of a coherent deposit on the platinum electrode. In acetonitrile, the insulating deposit formation proceeded above 20 mM monomer concentration. The differences in layer formation performed in acetic acid or ethyl acetate only allowed us to make estimations in a narrow range of the composition of their binary solvent mixtures utilizing the shape of curves related to guaiacol electropolymerization. Guaiacol was therefore not reliable in solvent composition estimations within the entire range. Due to its apolar nature, a poly (guaiacol) modified platinum macroelectrode was assessed for analyses in solutions prepared with organic solvents. The analytical performance of the modified electrode was tested with butylhydroxyanisole and butylhydroxytoluene. Linear sweep voltammetry was applied under stirred conditions, and the noise of stirring diminished compared with the bare electrode, although lower sensitivity was noticed.